Comparison of commercial nanoliquid chromatography columns for fast, targeted mass spectrometry-based proteomics. (June 2016) - Vehus, Tore; Seterdal, Kristina Erikstad; Krauss, Stefan; Lundanes, Elsa; Wilson, Steven R
Aim: We compared four commonly used, commercially available reverse phase nanoLC columns for identification/determination of Wnt/β-catenin-related pathway proteins.Materials & methods: The columns were: Chromolith ® (silica monolith; Merke Millipore, MA, USA), PepMap™ (porous particles; Thermo Fisher Scientific, MA, USA), Accucore™ (solid core particles; Thermo Fisher Scientific) and PepSwift™ (organic monolith; Thermo Fisher Scientific).Results: The peak capacity of the columns varied from 100 (Pepswift) to 190 (Accucore) (for 30 min gradients). All columns enabled identification/detection of GSK3β and β-catenin in the complex samples. However, even the columns with higher peak capacities could not enable detection of the somewhat less abundant proteins AXIN2 and TNKS2. The monoliths were more prone to retention time instability when sample complexity increased.Conclusion: We find that commercial nanoLC columns, although featuring different morphologies and peak capacities, provided surprisingly few practical differences for relatively fast, targeted determination of proteins. Lay abstract: The measurement of proteins (which can indicate diseases) in biological samples is commonly done with nonspecific approaches (can give rise to false results) that can be tedious and time consuming, especially when many proteins are to be measured from the same sample. Nanoliquid chromatography-mass spectrometry is an alternative approach that is very specific, and can be used to measure many proteins at once. There are several variants of nanoLC (i.e., nanoLC columns that are connected to the MS), but we have found that it is rather indifferent which nanoLC column is used for fast analysis. Hence, new nanoLC variants are called for to push the technique further.